A hybrid pixel detector with 4D information for dynamic synchrotron radiation applications. (1st September 2022) - Wei, W.; Zhang, J.; Cui, S.; Li, Z.; Li, M.; Wang, Y.; Wang, Z.; Jiang, X.; Zhu, K.; Liu, P.
Abstract: TETPIX is a hybrid pixel detector designed for dynamic synchrotron radiation applications. It is based on hit-driven readout scheme. 4D information of every incoming photon, including 2D position, timing, and energy, can be detected at the same time. The chip consists of a 64 × 32 pixel array with a pixel size of 150 μm × 150 μm. A module system is designed with a sensitive area of 2 cm × 2 cm, and tested at synchrotron radiation beamlines. The results show an energy resolution better than 16% over a range of 10–15 keV, and a capability of fine timing structure detection.